PEMBERDAYAAN EKONOMI POTENSIAL MASJID SEBAGAI MODEL PENGENTASAN KEMISKINAN - Rozzana Erziaty (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2015)
The research it aims to determine the potensial of mosque for can be mobilized into economic productive and strategy of economic potential that has been activated to be productive economy, the research is a qualitative with case studies. The analysis used is discriptif and SWOT analysis. With the result obtained the potential of the mosque is human resource, the management of organization mosque, assets of infrastructure of facilities generally, charity donation, give alms and teenagers the mosque, economic potensial the mosque is collected by ZIS payment outcomes based on samples taken by an average of Rp 22.574.920/mosque. With strategy the development of economic potensial to optimize the use of the management of the mosque to form the empowerment of like BMT are able to collect funds ZIS from donors and distribute it to economic activities, productive people in particular venture capital in poor as well as the development of the good manager and techinal assistent.